Editorial - Wit Pasierbek (Jesuit University Ignatianum in Krakow, 2017)
At the beginning of the 21 century a lot is being said about st dignity in its numerous varieties. Human dignity: of a woman, of a man, of a child constitutes the basis of any social, religious, legislative,orhistoricaldiscussions.Escalationandemphasison dignityissopowerful that it may appear that we have got lost in the basic understanding of this concept. Far too easily and too often are people lavish with this magnificent and significant attribute of human personality.